Anatomy of the leg and ankle: an introduction - Pather, Nalini (Henry Stewart Talks, 2021)
Anatomy of the leg and ankle, Bones of the leg and foot, Anatomy of the ankle joint, Muscles of the leg, Innervation of the leg